Latin American Political Science in a Comparative Perspective: Mapping the Peruvian Case - Rocha-Carpiuc, Cecilia (2025)
In recent decades, disciplinary studies on political science in Latin America have expanded rapidly. However, national case studies still predominate, and comparative analyses have only begun to emerge. The Peruvian case has received little attention in this literature and is rarely included in comparative studies, despite the discipline undergoing significant transformations in recent decades in this country. This article aims to fill this gap by providing an overview of the development and current state of political science in Peru from a comparative perspective, to situate it more precisely on the Latin American map while highlighting its particularities and challenges. After reviewing existing findings and offering a critical balance of prior research focused on political science in Peru, the article situates the case comparatively, exploring similarities and differences with other countries in the region based on evidence across several dimensions: institutionalization and professionalization; relations with the broader environment; teaching; academic production and research; and disciplinary analysis from a gender perspective. Methodologically, the article adopts a descriptive approach based primarily on an exhaustive review of secondary sources (both case–specific and comparative studies on political science in the region), complemented by primary sources to update the most recent information. The findings indicate significant advances in the institutionalization of the discipline in Peru over the last decade. However, essential challenges remain in comparison to countries where political science is more established. The article underscores the need for further research on dimensions that remain understudied in Peruvian disciplinary case studies, and advocates for the inclusion of Peru—as well as other countries with low or incipient institutionalization—into comparative disciplina.